Hip hop and music education: Where is race?. Issue 1 (1st August 2018) - Hess, Juliet
Engagement with hip hop – a cultural form that emerged from Black communities in New York City in the 1970s (Chang 2005) – as White listeners, musicians, educators and researchers requires asking thoughtful questions about race, racism and power. This introduction considers ethical issues that may arise from hip hop pedagogy and scholarship and explores the imperative to grapple with Whiteness when centring hip hop in our praxis. Power relations intricately shape hip hop education and hip hop research; as such, developing a practice of questioning and 'second guessing' ourselves as educators and researchers may allow us to develop an ethical practice for engaging with hip hop that centres race, racism and Whiteness, and refuses to reinscribe structural racist and salvationist power relations.